Genocide, Diversity, and John Dewey's Progressive Education. (October 2016) - Papastephanou, Marianna
Abstract: This article discusses how John Dewey's "Report and Recommendation upon Turkish Education" (published in 1924) and some of Dewey's related travel narratives reflect "civilizing mission" imperatives and involve multiple utopian operations that have not yet attracted political‐philosophical attention. Such critical attention would reveal Dewey's misjudgments concerning issues of diversity, geopolitics, and global justice. Based on an ethicopolitical reading of the relevant sources, the aim here is to expose developmentalist and colonial vestiges, to raise searching questions, and to obtain a heightened view on the stakes of Dewey's utopianism and progressive pragmatism. The article concludes that the acknowledgment of the Armenian genocide constitutes a major challenge to Dewey scholarship.